P377 Risk factors of rectal amputation for Crohn's disease with perianal lesion. (15th January 2020) - Yokoo, T; Yoshikawa, S; Masuda, T; Uchida, H; Nakao, T; Kashizuka, H; Yamaoka, K; Inagaki, M; Okamoto, K; Inatsugi, N
Abstract: Background: Recently, the importance of top-down therapy is emphasised for early Crohn's Disease (CD). Especially early use of biologics after onset may prevent rectal amputation or permanent stoma concrete of CD with perianal lesion (CDp). The aim of this study was to evaluate the risk factors of permanent stoma concrete for CDp, and especially we had an interest for the relationship between permanent stoma concrete and length of time it takes for infliximab (IFX) was started to use after onset. Methods: This is a comparative retrospective study of CDp patients who received IFX therapy at Kenseikai Nara Coloproctology Center between 2002 and 2018. We analysed risk factors of their rectal amputation using logistic regression analysis. Patients were included if they had perianal lesions and received IFX. The cases who received IFX after rectal amputation and who have missing values were excluded. Variables of interest included gender, age at onset and diagnosis, disease duration and location, disease behaviour, smoking, perianal surgical history, timing of IFX use after anoperineal lesion's onset. Late IFX use was defined as we started to use IFX 2 years after perianal lesion's onset. Results: Fifty-four patients were recruited. Mean age was 37 years old, the ratio of males to females was 3.5. Forty-one patients' disease was located in the small and large intestine, and thirteen patients' were located in the large intestine. Median follow-up duration was 149 months. Among 54 patients, 10 patients were received rectal amputation or permanent stoma concrete. The univariate analysis revealed that the risk factors for rectal amputation were smoking habit (OR 7.56, 95% CI 1.41–53.88, p -value = 0.007), penetrating type (OR 6.44, 95% CI 1.21–39.22, p -value = 0.013) and Late IFX use (OR 12.47, 95% CI 1.50–589.26, p = 0.011). A multivariate analysis revealed that smoking habit (OR 21.5, 95% CI 1.92–239, p = 0.013) smoking behaviour (OR 21.5, 95% CI 1.92–239.00, p = 0.013) and Late IFX use (OR 16.0, 95% CI 1.01–254, p = 0.049) were independent risk factor for rectal amputation (Table 1). Conclusion: Smoking and late IFX use may be a significant risk factor of rectal amputation for CDp. Early use of biologics may prevent permanent stoma concrete for CDp.